Enhancing heat transfer in microchannel heat sinks using converging flow passages. (1st March 2015) - Dehghan, Maziar; Daneshipour, Mahdi; Valipour, Mohammad Sadegh; Rafee, Roohollah; Saedodin, Seyfolah
Highlights: The fluid flow and conjugate heat transfer in microchannel heat sinks are studied. The Poiseuille and Nusselt numbers are presented for width-tapered MCHS. Converging walls are found to enhance the thermal performance of MCHS. The optimum performance of MCHS for fixed inlet and outlet pressures is discussed. For the optimum configuration, the pumping power is reduced up to 75%. Abstract: Constrained fluid flow and conjugate heat transfer in microchannel heat sinks (MCHS) with converging channels are investigated using the finite volume method (FVM) in the laminar regime. The maximum pressure of the MCHS loop is assumed to be limited due to constructional or operational conditions. Results show that the Poiseuille number increases with increased tapering, while the required pumping power decreases. Meanwhile, the Nusselt number increases with tapering as well as the convection heat transfer coefficient. The MCHS having the optimum heat transfer performance is found to have a width-tapered ratio equal to 0.5. For this tapering configuration and at the maximum pressure constraint of 3000 Pa, the pumping power reduces by a factor of 4 while the overall heat removal rate is kept fixed in comparison with a straight channel.